La escritura de abstracts y AIC de alumnos de ILE : análisis de escritos y evaluación de la efectividad de una pedagogía de género - Mirallas, Carolina (2017)
Scientific writing is a very complex albeit crucial activity for researchers who need to share findings and become a part of, or maintain, a position as members of a wide international discourse community. Since most scientific communication happens in English, the task of writing in this foreign language for researchers in Argentinian universities is a challenge for both researchers themselves and teachers of English who need to facilitate the writing path for students. With increasing evidence of its usefulness, Genre Pedagogy has been shown to greatly improve EFL (English as a Foreign Language) writing. In this research, the Sydney School Genre Pedagogy (SSGP) approach as offered by the Systemic Functional Linguistics (SFL) perspective is applied to the teaching of writing, with a twofold aim. A linguistic objective is pursued in analyzing student-produced abstracts and Scientific Research Articles (SRAs), with a special focus on interpersonal meanings and rhetorical components in student-produced scientific discourse. Second, this investigation assesses the effectiveness of SFL Genre Pedagogy in the teaching of one of the most important scientific genres used for the communication of findings, i.e. the SRA.